Intra articular hyaluronic acid versus intra articular triamcinolone hexacetonide in primary osteoarthritis of knee: a comparative study - Kizhedath, Sabeena; Valoth, Gopesh; Vasudevan, Bindhu (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Osteoarthritis (OA) is a painful, chronic disease with widespread burden on patients, communities, social and health care systems. Intraarticular (IA) Hyaluronic acid (HA) and corticosteroids are established treatments for OA knee. However, concerns exist regarding effect, duration, safety, effectiveness across population and heterogeneity. Aim of the study is to compare the efficacy and safety of IA HA with THA in the treatment of primary osteoarthritis knee. Methods: A descriptive cross-sectional study was done among 30 patients. One group (n=15) received IA THA 20mg/2mL on day 0 and other group (n=15) received IA HA 20mg/2 mL on day 0, 7 and 14 under aseptic precautions. The efficacy assessment using VAS for overall pain, joint line tenderness and 15m walking time in seconds were recorded. Side effects if any were noted. Results: Comparing both treatments IA THA provided superior short-term pain relief. But HA showed sustained benefit up to six months. Conclusions: OA being a chronic disease process, we need a drug which has a long-lasting effect. Additive effect of HA and THA can be considered for better efficacy.